The Best Solutions to Overcome the Lack of Scada Using Analytical Hirarchy Process (AHP): Case Study of SLN - Chevron - Harmen, Feri; Novani, Santi (The Indonesian Journal of Business Administration, 2016)
Abstract. Sumatra Light North is a portion of the operating area of PT Chevron Pacific Indonesia (CPI) which is located on the island of Sumatra, consisting of Bekasap area, Bangko area, Balam area, and Libo area, as well his production that far apart from each other then in need of an equipment for monitoring, controlling, analyzing the production in real time to maintain, improve and reduce the loss of production would require an technology SCADA (Supervisory control and Data Acquisition) which to date only 47% the number of wells already installed SCADA. The impact of the world oil price is getting down to $ 30 per barrel. SCADA development project then stopped. So there is a shortage of equipment SCADA. This study aims to select the best solution to overcome the shortcomings of the SCADA equipment. There are 4 ways to override it, i.e., new install, relocate, splitter and rental. The decision making process in this study is using Analytical Hierarchy Process (AHP) and Value-Focused Thinking (VFT) to select the best solution to overcome the shortage of equipment SCADA. Based on the analysis calculations using AHP four criteria and interviews of experts, the best solution to overcome the problem of shortage of SCADA equipment is to perform SCADA equipment rental. Keywords: SLN Chevron, Oil Well, SCADA Equipment, Value focused thinking, Analytic hierarchy process Abstract. Sumatra Light North is a portion of the operating area of PT Chevron Pacific Indonesia (CPI) which is located on the island of Sumatra, consisting of Bekasap area, Bangko area, Balam area, and Libo area, as well his production that far apart from each other then in need of an equipment for monitoring, controlling, analyzing the production in real time to maintain, improve and reduce the loss of production would require an technology SCADA (Supervisory control and Data Acquisition) which to date only 47% the number of wells already installed SCADA.The impact of the world oil price is getting down to $ 30 per barrel. SCADA development project then stopped. So there is a shortage of equipment SCADA. This study aims to select the best solution to overcome the shortcomings of the SCADA equipment. There are 4 ways to override it, i.e., new install, relocate, splitter and rental.The decision making process in this study is using Analytical Hierarchy Process (AHP) and Value-Focused Thinking (VFT) to select the best solution to overcome the shortage of equipment SCADA.Based on the analysis calculations using AHP four criteria and interviews of experts, the best solution to overcome the problem of shortage of SCADA equipment is to perform SCADA equipment rental. Keywords: SLN Chevron, Oil Well, SCADA Equipment, Value focused thinking, Analytic hierarchy process